COORDINATION MEETING AND JOINT OPERATIONS OF THE FOREIGNER SUPERVISION TEAM (TIMPORA) IMMIGRATION OFFICE CLASS I BORDER CONTROL MALANG - Pandu Prasetyo Wibowo; Hanifa Maulida (Jurnal Abdimas Imigrasi, 2021)
the purpose of the implementation of this activity is to carry out supervision in order to enforce immigration law in the area of the Immigration Office Class I TPI Malang. coordination between government agencies and owners/managers/inn providers and companies in the context of supervising the presence and activities of foreign nationals in the area of the Immigration Office Class I TPI Malang. This Foreigner Supervision activity is part of the effort to realize the improvement of security order and stability in the region in order to anticipate the negative influence of the presence and activities of foreigners, exchange of information and a comprehensive inventory of problems related to the presence and activities of foreigners in the Immigration Office area of class 1 TPI Malang.